Single genetic locus improvement of iron, zinc and β-carotene content in rice grains - Singh, Simrat Pal (Sci Rep, 2017)
Nearly half of the world’s population obtains its daily calories from rice grains, which lack or have insufficient levels of essential micronutrients. The deficiency of micronutrients vital for normal growth is a global health problem, and iron, zinc and vitamin A deficiencies are the most prevalent ones. We developed rice lines expressing Arabidopsis NICOTIANAMINE SYNTHASE 1 (AtNAS1), bean FERRITIN (PvFERRITIN), bacterial CAROTENE DESATURASE (CRTI) and maize PHYTOENE SYNTHASE (ZmPSY) in a single genetic locus in order to increase iron, zinc and β-carotene content in the rice endosperm. NAS catalyzes the synthesis of nicotianamine (NA), which is a precursor of deoxymugeneic acid (DMA) iron and zinc chelators, and also chelate iron and zinc for long distance transport. FERRITIN provides efficient storage of up to 4500 iron ions. PSY catalyzes the conversion of GGDP to phytoene, and CRTI performs the function of desaturases required for the synthesis of β-carotene from phytoene. All transgenic rice lines have significantly increased β-carotene, iron, and zinc content in the polished rice grains. Our results establish a proof-of-concept for multi-nutrient enrichment of rice grains from a single genetic locus, thus offering a sustainable and effective approach to address different micronutrient deficiencies at once.